2019
DOI: 10.1051/0004-6361/201834446
|View full text |Cite
|
Sign up to set email alerts
|

Modeling sulfur depletion in interstellar clouds

Abstract: Context. The elemental depletion of interstellar sulfur from the gas phase has been a recurring challenge for astrochemical models. Observations show that sulfur remains relatively non-depleted with respect to its cosmic value throughout the diffuse and translucent stages of an interstellar molecular cloud, but its atomic and molecular gas-phase constituents cannot account for this cosmic value towards lines of sight containing higher-density environments. Aims. We have attempted to address this issue by model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
157
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(164 citation statements)
references
References 125 publications
7
157
0
Order By: Relevance
“…C.N.S. thanks the Alexander von Humboldt Foundation for their generous support and both K. Laas & Caselli (2019) and Semenov et al (2010). Table 7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C.N.S. thanks the Alexander von Humboldt Foundation for their generous support and both K. Laas & Caselli (2019) and Semenov et al (2010). Table 7.…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the role of radiation chemistry and non-diffusive bulk reactions on the abundances of sulfur species in dense interstellar regions, we have run simulations of generic cold cores using physical conditions and initial elemental abundances taken from Laas & Caselli (2019), and listed in Tables 2 and 3. We have carried out five sets of simulations, as listed in Table 4.…”
Section: Physical Conditions and Model Detailsmentioning
confidence: 99%
“…Sulphur abundance. A large theoretical and observational effort has been done in the last five years to understand the sulphur chemistry that is progressively leading to a new paradigm (Vidal et al 2017;Fuente et al 2016Fuente et al , 2019Le Gal et al 2019;Laas & Caselli 2019). Gas-grain models provide a new vision of the interstellar medium in which both gaseous and ice species are predicted.…”
Section: Discussion: Is H 2 S Tracing the Snow Line In Dark Cores?mentioning
confidence: 99%
“…One first result is that our models overestimate by more than one order of magnitude the CS abundance in TMC 1 and Barnard 1b. The problem of the overestimation of the CS abundance was already pointed out by Vidal et al (2017) and Laas & Caselli (2019). Vidal et al (2017) suggested that it could come from wrong branching ratios of the dissociative recombination of HCS + or a potentially new sink for CS that might be the O + CS reaction whose reaction rate has not been measured at low temperatures.…”
Section: Chemical Desorption: 1d Modelingmentioning
confidence: 99%
“…However, the chemistry in star-forming regions has been poorly understood at least until quite recently because the abundances of the observed sulphurbearing molecules in these sources accounted only for a small fraction of the total sulphur budget whose depletion into dust grains has been poorly constrained [5−7]. Considerable progress has been made over the years, particularly in a recent contribution [8].…”
Section: Introductionmentioning
confidence: 99%